STRATEGI DAN PENDEKATAN GURU PENDIDIKAN AGAMA ISLAM DALAM PEMBINAAN KEBERAGAMAAN REMAJA - Arni Zulianingsih (Universitas Islam Sultan Agung, 2019)
The Strategy and Approach of Teachers of Islamic Education in Youth Religious Development is qualitative research that aims to describe the phenomenon and context in implementing religious formation. This research is a case study because the focus of this study answers the question of